Building for Birds Evaluation Tool: Breeding and Wintering Habitat for Forest Birds - Mark Hostetler; Jan-Michael Archer (EDIS, 2017)
Several bird species use forest fragments and trees conserved in built areas as breeding, wintering, and stopover habitat. Scientists have created a Building for Birds online tool to help these birds and the people who appreciate them. This evaluation tool is most useful for small developments or developments in already fragmented landscapes.